Current Volumetric Models Overestimate Vestibular Schwannoma Size Following Stereotactic Radiosurgery. Issue 2 (February 2020) - Sherry, Alexander D.; Khattab, Mohamed H.; Totten, Douglas J.; Wharton, David M.; Luo, Guozhen; Manzoor, Nauman F.; Rivas, Alejandro; Chambless, Lola B.; Davis, Larry T.; Attia, Albert; Cmelak, Anthony J.
Abstract : Objective: Accurate volume assessment is essential for the management of vestibular schwannoma after stereotactic radiosurgery (SRS). A cuboidal approximation for volume is the standard surveillance method; however, this may overestimate tumor volume. We sought to evaluate several volumetric models and their suitability for post-SRS surveillance. Study Design: Retrospective cohort study. Setting: Tertiary referral center. Patients: We evaluated 54 patients with vestibular schwannoma before and after SRS. Intervention(s): Gold-standard volumes were obtained by a radiation oncologist using contouring software. Volume was also calculated by cuboidal, ellipsoidal, and spherical formulae using tumor diameters obtained by a neuroradiologist. Main Outcome Measure(s): Percent error (PE) and absolute percent error (APE) were calculated. Paired t test evaluated bias, and the Bland–Altman method evaluated reproducibility. Linear regression evaluated predictors of model error. Results: All models overestimated volume compared with the gold standard. The cuboidal model was not reproducible before SRS ( p  < 0.001), and no model was reproducible after SRS (cuboidal p  < 0.001; ellipsoidal p  = 0.02; spherical p  = 0.02). Significant bias was present before SRS for the cuboidal model ( p  < 0.001), and post-SRS for all models [cuboidal ( p  < 0.001), ellipsoidal ( p  < 0.02), and spherical ( p  = 0.005)]. Model error was negatively associated with pretreatment volume for the cuboidal (PE p  = 0.03; APE p  = 0.03), ellipsoidal (PE p  = 0.03; APE p  = 0.04), and spherical (PE p  = 0.02; APE p  = 0.03) methods and lost linearity post-SRS. Conclusions: The standard cuboidal practice for following vestibular schwannoma tumor volume after SRS overestimates size. Ellipsoidal and spherical estimations have improved performance but also overestimate volume and lack reliability post-SRS. The development of other volumetric models or application of contouring software should be investigated.